Django 2 by Example : Build powerful and reliable Python web applications from scratch. - Mele, Antonio (Packt Publishing, 2018)
Django is a powerful Python web framework designed to develop web applications quickly. If you want to learn about the entire process of developing professional web applications with Django, then this book is for you. This book will walk you through the creation of four professional Django projects, teaching you how to solve common problems ...